Association between preoperative albumin and postoperative pneumonia in patients undergoing major non-cardiac surgery - Pang, Qian-Yun; Feng, Yu-Mei; Yang, Ya-Jun; Liu, Hong-Liang (Frontiers in Nutrition, 2025)
BackgroundPostoperative pneumonia is a common and serious complication following non-cardiac surgery. However, the relationship between preoperative albumin levels and postoperative pneumonia remains unclear in major non-cardiac surgeries, and the cut-off value for predicting postoperative pneumonia has yet to be determined.MethodsData from patients who underwent non-cardiac surgery between January 1, 2019, and December 31, 2022, were extracted from the institutional electronic medical records of Chongqing University Cancer Hospital. The primary exposure of interest was preoperative albumin levels, and the outcome was postoperative in-hospital pneumonia.ResultsThe results revealed a non-linear dose–response relationship between preoperative albumin levels and postoperative pneumonia. A 1 g/L increase in preoperative albumin levels was associated with a 4.4% reduction in adjusted odds ratio (aOR) of postoperative pneumonia (aOR: 0.956, 95% CI: 0.940–0.973, p < 0.001). Patients with preoperative albumin levels <38.9 g/L or between 38.9 and 45.3 g/L had a 67.4 and 30.3% higher OR, respectively, compared to those with levels >45.3 g/L (aOR: 1.674, 95% CI: 1.313–2.135, p < 0.001; and aOR: 1.303, 95% CI: 1.045–1.624, p = 0.019). Subgroup analyses indicated that the risk of developing pneumonia was more pronounced in younger, female, and healthier patients.ConclusionThese findings suggest that preoperative albumin levels are significantly associated with the development of postoperative pneumonia in patients undergoing major non-cardiac surgery. A preoperative albumin level of <45.3 g/L may serve as a predictive marker for postoperative pneumonia.